Ryzyko podatkowe w wydawnictwie elektronicznym - Kotyla, Cyryl; Ossowski, Marek (Tax Risk in Electronic Publishing House, 2006)
Electronic publishing business is quite new in Poland as well as worldwide. Finance managing of this kind of companies is quite complicated but it becomes even more, in case of a new publishing house which develops a new electronic product. Production of such a product takes long time which means that a developer (company) reports loses during the first few periods for both i.e. accounting and income company tax purposes. Due to this, because Polish Tax Office does not accept companies which report tax loses, companies have to face a tax risk, which should be understood as a risk of paying future penalties as a result of wrong tax law interpretation made in the past. A mistake could be made by companies themselves as well as by Tax Office as production process and classification of its expenditures is not obvious and clear enough on current Polish taxation law bases in force. This article describes a situation of a new publishing house and its problem with Tax Office during the time of a new product preparation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 347-356